2002
DOI: 10.1002/mrd.90002
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Na,K‐ATPase α4 isoform and the Na+/H+ exchanger in sperm motility

Abstract: The Na,K-ATPase generates electrochemical gradients that are used to drive the coupled transport of many ions and nutrients across the plasma membrane. The functional enzyme is comprised of an alpha and beta subunit and families of isoforms for both subunits exist. Recent studies in this laboratory have identified a biological role for the Na,K-ATPase alpha4 isoform in sperm motility. Here we further investigate the role of the Na,K-ATPase carrying the alpha4 isoform, showing again that ouabain eliminates sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 55 publications
3
103
0
Order By: Relevance
“…Previous studies have explored the function of α4 using selective pharmacological inhibition of this isoform with ouabain (7,11,12,20). More recently, we have investigated the function of α4 using a mouse model with increased expression of the rat α4 isoform in sperm (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the function of α4 using selective pharmacological inhibition of this isoform with ouabain (7,11,12,20). More recently, we have investigated the function of α4 using a mouse model with increased expression of the rat α4 isoform in sperm (15).…”
Section: Discussionmentioning
confidence: 99%
“…Babcock et al [106,107] suggested that the mechanism for proton efflux from bovine sperm was via a voltage-gated proton channel, based on the fact that the sperm cytosol becomes alkaline upon membrane depolarization [106,107]. Later studies focused on the role of sperm-specific Na + /H + (sNHE) and Cl − /HCO 3 − exchangers as potential mechanisms for intracellular alkalization in rodent spermatozoa [32,108,109]. Due to the increase in external Na + upon ejaculation and its flagellar localization, the NHE was proposed as potential mechanism for sperm alkalization.…”
Section: Mechanisms Of Proton Extrusion From Mammalian Spermmentioning
confidence: 99%
“…In brief, cells were treated with ammonium choline solution (50 mM NH 4 Cl, 80 mM choline chloride, 1 mM MgCl 2 , 2 mM CaCl 2 , 5 mM glucose, 20 mM HEPES-Tris, pH 7.4) for 20 min at 37°C followed by a rapid washout with isotonic choline chloride solution (130 mM choline chloride, 1 mM MgCl 2 , 2 mM CaCl 2 , 5 mM glucose, 20 mM HEPES-Tris, pH 7.4) to acutely acidify the cytosol. Assays were immediately initiated by adding radioactive 22 Na ϩ (1 Ci/ml 22 NaCl in choline chloride solution) to each well in the absence or presence of 1 mM amiloride. After 5 min, the influx of 22 Na ϩ was terminated by rapidly washing each well three times with ice-cold NaCl-saline solution (130 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 2 mM CaCl 2 , 5 mM glucose, 20 mM HEPES-NaOH, pH 7.4).…”
Section: Namentioning
confidence: 99%
“…NHE5 was identified as a unique member of the NHE gene family whose mRNA is expressed almost exclusively in the brain (19,20), although more recent studies have suggested that NHE5 might be functional in other cell types such as sperm (21,22) and osteosarcoma cells (23). Curiously, mutations found in several forms of congenital neurological disorders such as spinocerebellar ataxia type 4 (24 -26) and autosomal dominant cerebellar ataxia (27)(28)(29) have been mapped to chromosome 16q22.1, a region containing NHE5.…”
mentioning
confidence: 99%